ЭFFICACY AND TOLERABILITY OF LENVATINIB IN RADIOIODINE-REFRACTORY DIFFERENTIATED THYROID CANCER (Western European Journal of Medicine and Medical Science, 2024)
The introduction of tyrosine kinase inhibitors into clinical practice has significantly improved treatment outcomes for patients with radioiodine-refractory differentiated thyroid cancer (RR-DTC). Lenvatinib is recommended as a first-line drug for this category of patients